Identification of fungi associated with dry rot disease of yam under storage conditions - Sánchez López, Diana Beatriz (2020)
Dry rot of yam tubers is a disease that currently causes the greatest economic losses to small producers associated with this crop in the Colombian Caribbean, as it deteriorates the internal tissues of tubers, causing loss of its commercial value and the seeds. Currently, we are not certain about the identity of the causal agents, so this research was carried out in order to objetive collect, isolate and characterize the fungi associated with the dry rot disease of yam tubers cv. "Espino" in the Caribbean region of Colombia in storage conditions. This study was carried out between February and October 2019, identifying the yam-producing areas in the Colombian Caribbean region and collecting in the municipalities and sidewalks, tubers in storage. In laboratory, the associated fungi were isolated from the lesions and identified through the amplification of the ITS (Internal Transcribed Spacer) region of the ribosomal DNA, complemented by the Calmodulin and β-tubulin gene 2.  A total of 56 fungi associated with lesions were isolated, which were grouped into 10 morphotypes, achieving their classification by genus and species. According to our results, the species DH2-Lasiodiplodia theobromae, DH3-Fusarium solani, and DH6-Neocosmospora rubicola were identified as the main causal agents associated to dry rot disease of yam tubers under storage conditions in the Colombian Caribbean region.